A Methodology for software reuse (Master of Software Engineering, unofficial) - Nakano, Hozumi (My University, 2006)
Software reuse has been practiced in industries with or without clear identification of reuse. In most cases, software reuse process uses design and code components, particularly the latter. From the literature survey, it was observed that there is no software reuse methodology that can be applied throughout the software life cycle. It was therefore decided to develop a reuse methodology that can be applied to the entire software life cycle. This research started by observing two pairs of industry software products one reusing the other. The reusability score was computed in each case and was confirmed to be satisfactory by the development team. Based on the results, a reuse methodology that can be applied to the entire software life cycle was proposed. The methodology gives a set of guidelines for a formal reuse process. This process assumes that the requirements for the new product to be developed are written first, and then the reusable software components can be searched in a reuse repository. This repository is assumed to include all components of existing products such as requirements, design, code, test cases and so on. The proposed methodology guides developers to identify reusable software artifacts and tailor them toward the new product.
Keywords: Computer software -- Reusability